Ownership in The Draft of Civil Code in Serbia - Popov, Danica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
The article is about Basic provisions of ownership in The Draft of Civil Code.  The author analyzed article in The Draft of Civil Code and try to offer better solutions. Ownership in The Draft of Civil Law in Serbia is define as  exclusive right of natural persons and legal entities to possess, use and dispose with his  thing within the limits prescribed by law. Ownership may be described as the entirety of powers of use and disposal allowed by law. Ownership is exclusive right to possess, use and dispose of property subject only to the rights of persons having a superior interest and to any restrictions on the owner-s rights imposed by agreement with or by act of third parties or by operation of law. Ownership is one of the very important human rights. The presumption is that the owner is not limited in use of his own think. The owner shall acquire the ownership rights in accordance with the nature and purpose of the think. Everybody shell be obliged to sustain from infringing the ownership rights of another. The ownership rights may be taken away or restricted in accordance with the Constitution and Law. Exercising of the ownership right contrary of the purpose of which it has been established or recognized shell be forbidden. Ownership is always subject to the rule that owner must so use own property as not to injure his neighbor.